PENDAMPINGAN IBU HAMIL SEBAGAI UPAYA MENURUNKAN KECEMASAN MENGHADAPI PERSALINAN - -, Ari Sulistyawati (ABDIMAS Madani, 2022)
Labor is a normal cycle in pregnancy that requires physical and mental readiness. The perception that childbirth is a painful cycle is still a cause of anxiety for pregnant women. Knowledge about prenatal care and how to deal with childbirth effectively is needed by pregnant women. The presence of a companion at the end of pregnancy is very helpful for pregnant women to learn and prepare for childbirth. This community service activity aims to reduce the anxiety of pregnant women facing childbirth. The method used in this activity is to provide education and counseling for pregnant women who are members of the WhatsApps group My Amazing Birth. Education is carried out continuously every day for six months through WhatsApps lectures for classical. Counseling is done privately through private chat and telephone connections, both voice and video. This activity was attended by 94 pregnant women in the third trimester. The results showed that there was a decrease in the anxiety of pregnant women in the form of a decrease in the proportion of pregnant women with high anxiety levels from 32.9% (31 people) to zero, which means it shifted down to moderate anxiety levels. Meanwhile, the proportion of moderate anxiety level which was originally 45.3% (43 people) to 22.3% (21 people), or 22.7% shifted to a mild anxiety level. After participating in this activity, pregnant women experienced a decrease in anxiety and increased readiness to face childbirth. It is hoped that pregnant women can access the community or childbirth preparation assistance classes so that they have sufficient knowledge and get a positive impact from interactions with companions and fellow participants.